Tra genere e generi Tradurre e pubblicare testi per ragazze e ragazzi - Pederzoli, Roberta; Illuminati, Valeria (Lingua, traduzione, didattica, 2021)
This open access book explores the translation of children's and Young Adult literature from a gendered perspective. By combining Translation Studies, Literary and Gender Studies, it provides original interdisciplinary analyses on a variety of literary and non-literary texts for children's and Young Adults, translated from French, English and Spanish into Italian. It sheds new light on a research area that has so far been little investigated at international level, and especially in the Italian academic context. The book also includes a document inspired by the "Polite Code" which aims to help publishers and translators to promote inclusion, respect diversities, and adopt a gender-sensitive approach when publishing and translating for young readers. The book is the result of an AlmaIdea research project, funded by the University of Bologna.